The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1222900110
|View full text |Cite
|
Sign up to set email alerts
|

H–Y antigen-binding B cells develop in male recipients of female hematopoietic cells and associate with chronic graft vs. host disease

Abstract: B cells are known to play an important role in pathogenesis of human chronic graft vs. host disease (cGVHD). Our group has previously shown that IgG allo-antibodies recognize Y chromosomeencoded proteins (H-Y) and a dominant H-Y epitope, DEAD box protein (DBY-2) detectable 6-12 mo after transplant in male patients who receive grafts from female donors (F→M) hematopoietic cell transplantation (HCT). Here we present FACS studies of peripheral blood mononuclear cells collected 6 mo after transplant showing that 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…The correlative biological analysis of HY-Abs supports the allogeneic B-cell pathogenic role in independent prospective trials for cGVHD prophylaxis and treatment. 9,24,29,30 HY-Abs would serve as a prognostic biomarker for cGVHD and an immunologic indicator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlative biological analysis of HY-Abs supports the allogeneic B-cell pathogenic role in independent prospective trials for cGVHD prophylaxis and treatment. 9,24,29,30 HY-Abs would serve as a prognostic biomarker for cGVHD and an immunologic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior studies have demonstrated that HY-Abs were detected in F→M HCT patients, 8,9 but the temporal association between HY-Ab development and cGVHD has yet to be established. In addition, prior studies were limited by antibody detection technologies and by measurement of HY-Abs in blood samples collected $9 months after HCT.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…47,48,102,103 Autoantibodies are widely detected in patients with cGVHD. Although initial reports suggested that antibodies to the platelet-derived growth factor receptor may be pathogenic, 104 this finding has been debated.…”
Section: Org Frommentioning
confidence: 99%
“…[1][2][3][4][7][8][9][10] This adverse effects of Female→Male HCT are thought to result from allogeneic immune responses against minor histocompatibility antigens encoded on the Y-chromosome of a male recipient (H-Y antigens). 7,[11][12][13][14] To avoid these post-HCT complications or to reduce disease relapse, various conditioning types have developed. 15 Non-myeloablative conditioning regimens such as total lymphoid irradiation and anti-thymocyte globulin (TLI-ATG) conditioning have shown promise as a method to reduce GVHD incidence and non-relapse mortality.…”
Section: Introductionmentioning
confidence: 99%